Relación de la variabilidad de la frecuencia cardiaca y el yo-yo test en deportistas universitarios - Salazar Orellana, Cristian; Díaz Coria, Gastón; Garrido Osorio, Víctor; dos Santos Carvalho, Anderson; Benavides Roca, Luis (Retos, 2026)
Introduction: Heart rate variability (HRV) reflects autonomic modulation and is associated with physical fitness, particularly in aerobic endurance disciplines. However, the relationship between HRV and performance in aerobic capacity tests, such as the Yo-Yo test, has not been fully explored in university athletes.Objective: To analyze the relationship between resting HRV parameters and performance in the Yo-Yo test among university athletes.Methodologic: A cross-sectional correlational study was conducted with 30 male athletes (aged 18–26 years). HRV was assessed in supine and standing positions using time-domain and frequency-domain analyses (SDNN, RMSSD, pNN50%, HF, LF, VLF, and the LF/HF ratio). Subsequently, the maximum velocity reached in the Yo-Yo Intermittent Recovery Test Level 2 (YIRT2) was recorded. Pearson’s correlation test (p